Analisis Peran Sistem Keuangan Desa Untuk Meningkatkan Tata Kelola Pemerintahan Yang Baik Melalui Akurasi Dan Akuntabilitas Pelaporan Keuangan Pemerintah - Gede Sanjaya Adi Putra; I Gusti Ngurah Sanjaya; Cokorda Krisna Yudha (Fakultas Ekonomi Universitas Negeri Manado, 2024)
This study explores the role of financial report accuracy, accountability, and the implementation of village financial systems in promoting good governance in the management of village funds..A mixed-methods approach combining qualitative and quantitative techniques with a descriptive method was employed, involving 172 respondents from villages in the Denpasar area. The findings reveal that while village financial systems do not directly influence the implementation of good governance, they improve the quality of village financial reports, serving as a mediating variable in supporting good governance practices. The study recommends strengthening human resource capacity in accounting, providing technical support from the Financial and Development Supervisory Agency, and fostering village commitments to transparent financial reporting to build public trust and reinforce good governance implementation.